Temperature and pH Effect on the Sorption of Divalent Metal Ions by Silica Gel - S. Mustafa; B. Dilara; A. Naeem; N. Rehana; K. Nargis (Adsorption Science & Technology)
The sorption of Zn 2+ , Ni 2+ and Cd 2+ ions by silica gel was studied as a function of ion concentration, pH and temperature. An increase in all three parameters led to an increase in the extent of sorption for all the metal cations studied. The selectivity of the solid was observed to be in the order Zn 2+ > Ni 2+ > Cd 2+ . Sorption of the metal cations was accompanied by the release of H + ions into the bulk phase. On average two moles of H + ions were released per mole of metal cation sorbed. The sorption data fitted the linear forms of both the Kurbatov and Langmuir adsorption equations. The values of the binding constants were used to estimate the apparent thermodynamic parameters, ΔH and ΔS, for the adsorption process. FT-IR spectroscopic studies also showed that the uptake of metal cations by the silica gel occurred via a cation-exchange process.